Anfibios y reptiles de Oaxaca. Lista, distribución y conservación. - Casas-Andreu, Gustavo; Méndez De La Cruz, Fausto R.; Camarillo, José Luis (Instituto de Ecología, A.C., 1969)
The herpetofauna of Oaxaca is composed by 40 families, 127 genera and 359 species (33% amphibians and 67% reptiles). This fauna comprises 35.7% of the Mexican herpetofauna. This is one of the richest faunas in Mesoamerica, only exceded by that of Costa Rica. Oaxaca was divided by other authors in 10 floristic regions . Amphibians and reptiles were analyzed following these subdivitions. It was found that the herpotofauna it with that pattern, because the similarity coefficients between regions are very low, so 10 herpetofaunistic regions are also recognized. The most diverse regions are the Sierra Madre de Oaxaca with 43 species of amphibians and 60 of reptiles, The Istmo de Tehuantepec having 27 species of amphibians and 106 of reptiles and the Sieira Madre del Sur with 24 species of amphibians and 49 of reptiles. The planicie costera del pacífico also contains an important number of species. Regions as the Valley of Tehuacán Cuicatlán Valley, Balsas Depression and the Central Valleys have been poorly, studied and our results on these regions are preliminary. Elevationally, the most diversified horpetofauna is between sea level and 1000 m.